Sodium bicarbonate ingestion alters the slow but not the fast phase of VO2 kinetics - Berger, N. J. A.; McNaughton, L. R.; Keatley, S.; Wilkerson, D. P.; Jones, A. M. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The influence of metabolic alkalosis (ALK) on pulmonary O2 uptake (pVO2) kinetics during high-intensity cycle exercise is controversial. The purpose of this study was to examine the influence of ALK induced by sodium bicarbonate (NaHCO3) ingestion on pVO2 kinetics, using a sufficient number of repeat-step transitions to provide high confidence in the results obtained.